The Effect of Compensation and Work Culture on The Performance of Honorary Teacher Vocational School, Serang City, Banten Province - Romlah Virdaningsih; Heru Santosa; Masduki Ahmad (Peneliti.net, 2020)
The purpose of this study is to understand the Effect of Compensation And Work Culture On Teacher Performance. This is a quantitative research using a questionnaire method conducted at the vocational school (SMK) of Serang, Banten Province in 2019. Data were collected through participant observation using a questionnaire, observation, document study. Analysis and interpretation of the data shows that (1) The increase in compensation received by teachers of Serang City Vocational Schools in Banten Province causes an increase in the performance of these teachers. (2) A high work culture will improve the performance of vocational school (SMK) of Serang, Banten Province. (3) Increasing compensation will improve the work culture of Serang Vocational School in Banten Province.The findings lead to recommendations for the provincial government to increase the value of compensation for teachers in accordance with the UMP, principals in order to maintain and preserve a work culture of teachers who are in good condition, instilling an attitude of initiative from the teacher's person to always improve their knowledge, abilities, skills and skills in carrying out tasks